الوحدة النحوية المتكلِّسة في العربية المُلْتبسة بنواسخ الابتداء (كان وأخواتها) أنموذجا - حميدي, خالد كاظم; الخفاجي, تومان غازي (Revues faculté des lettres et des langues; Vol. 1 No 21 (2017): مجلة كلية الآداب و اللغات, 2018)
ABSTARCT: This study deals with the linguistic phenomenon we call (the phenomenon of Stereotypie) and strength, According to research hypothesis we intend to prove with the help of the historical method and Comparative that the Arabic language in one of the stages of change Auxiliary verbs being in the sentence, and then re-employ these tools for the purposes of rhetorical having lost the original sense. The advantage of burners not to change any of the racist movement sentence. And erred as traditional grammar in measured on the familiar tools structure led to the complexity of the study and the loss of sense, has carried out this research to solve this problem, a scientific hypothesis has undertaken research in recognized experimentation and discovered its system which is going whereby for the production of meaning primarily laws which (absolute emphasis) which is not likely truth and lies including, inter alia, about the meanings of news reporting to the meaning construction sentence. الملخص يعنى هذا البحث بدراسة ظاهرة لغوية مستقلة سمّيناها (ظاهرة التكلس) وقوامها بحسب فرضية البحث التي سنثبتها بمعونة المنهج التاريخي والمقارن أنّ اللغة العربية في إحدى مراحل تغيرها تخلّت عن فعل الكينونة المساعد في جملتها الاسمية، ثم أعادت توظيف هذه الأدوات لأغراض بلاغية بعد أنْ فقدت معانيها الأصلية. وميّزتها اللغة من النواسخ بعدم مساسها بحركة أيّ من عنصري الجملة الاسمية. وقد أخطأ النحو التقليدي في قياسها على بنية النواسخ ما أدّى إلى تعقيد دراستها وضياع معانيها، وقد اضطلع هذا البحث بحلّ هذه المشكلة، بفرضية علمية اضطلع البحث في إثباتها تجريبا واكتشف قوانين نظامها الذي تسير بموجبه لإنتاج المعنى المقامي المقصود وهو (التوكيد المطلق) الذي لا يحتمل الصدق والكذب بما يقرِّب معاني جملتها الخبرية إلى معنى الجملة الإنشائية، ولكنّ بنيتها بنية جملة خبرية.